Targeting ferroptosis: a promising approach for treating lung carcinoma - Ziyang Wu; Yan Zhang; Wendi Zhong; Kunjian Wu; Tian Zhong; Tao Jiang (Cell Death Discovery)
Abstract Lung carcinoma incidence and fatality rates remain among the highest on a global scale. The efficacy of targeted therapies and immunotherapies is commonly compromised by the emergence of drug resistance and other factors, resulting in a lack of durable therapeutic benefits. Ferroptosis, a distinct pattern of cell death marked by the buildup of iron-dependent lipid peroxides, has been shown to be a novel and potentially more effective treatment for lung carcinoma. However, the mechanism and regulatory network of ferroptosis are exceptionally complex, and many unanswered questions remain. In addition, research on ferroptosis in the diagnosis and treatment of lung cancer has been growing exponentially. Therefore, it is necessary to provide a thorough summary of the latest advancements in the field of ferroptosis. Here, we comprehensively analyze the mechanisms underlying the preconditions of ferroptosis, the defense system, and the associated molecular networks. The potential strategies of ferroptosis in the treatment of lung carcinoma are also highlighted. Targeting ferroptosis improves tumor cell drug resistance and enhances the effectiveness of targeted drugs and immunotherapies. These findings may shed fresh light on the diagnosis and management of lung carcinoma, as well as the development of drugs related to ferroptosis.